Contour Integration and Consequences of Cauchy's Residue Theorem in Mathematical Physics - Shehu, Ndam George; Haggai, Manjak Nibron; Sanda, Adamu Muhammad; Zuwaira, Babawuro (Mikailalsys Journal of Advanced Engineering International, 2025)
This research presents an in-depth exploration of contour integration and the applications of Cauchy’s Residue Theorem within the field of complex analysis, with particular attention to their relevance in mathematical physics. The study begins by establishing a rigorous theoretical foundation, addressing key concepts such as analytic functions, singularities, and essential theorems underpinning contour integration. Central to the analysis is the evaluation of complex integrals using the residue theorem and the practical application of Cauchy’s integral formula in solving definite integral problems. Applied examples are drawn from complex integration scenarios and fluid dynamics, where these methods are employed to address definite integral equations and potential flow models. The findings highlight the efficacy and significance of Cauchy's Residue Theorem in solving contour integration problems in the complex plane. Furthermore, the study contributes to a deeper understanding of analytic functions and complex potentials, offering valuable insights for future research involving the modeling of physical systems through complex analysis techniques.